Services Liberalization in the EU and the WTO Concepts, Standards and Regulatory Approaches - Klamert, Marcus 1974- (Cambridge University Press, 2014)
Both in WTO law and EU law there is a dichotomy between liberalisation based on market access and targeting domestic regulation. Consequently, both regimes share the problem of distinguishing national measures impairing market access and those that do not have such effect. Looking at the provision of services, a cornerstone of EU substantive law, in the EU and the WTO this book offers a comprehensive evaluation of the current legal status quo on transnational services provision on a global level. Based on thorough analysis of both EU and WTO law, policymakers are provided with concrete proposals for fostering the consistency and effectiveness of the current regime. A final chapter discusses possible approaches to regulation such as home state rule, host state rule and mutual recognition from a comparative perspective. Written by a highly respected author team, this is essential reading for EU internal market specialists and WTO law scholars alike
Title from publisher's bibliographic system (viewed on 12 Feb 2016)
Keywords: Europäische Union; World Trade Organization; Foreign trade regulation; Außenhandelsrecht; Dienstleistungssektor